Pre-Fetch Data Caching Strategy in Mobile Database System for Integrity Constraints Checking - Zarina, Dzolkhifli; Wan Nurul Safawati, Wan Manan; Mohd Hafiz, Mohd Hassin; Hamidah, Ibrahim (2015)
A database must always in stable state, consistent and reliable. An integrity constraint checking is an important issue that must be addressed in order to maintain the database consistency. Due to various constraints inherited from limitations of wireless communication and mobile devices, it is a challenge on maintaining data consistency in databases. One of limitation of mobile devices that is looked into is limited storage capabilities, a mobile host is not capable of storing all data items in the network, thus it must share some data item with a database in the fixed network. Data caching technique is used to cache frequently accessed data from the base station into mobile host. By caching only the needed data items during integrity constraints checking, it allows mobile host to continue processing without worrying about disconnection. The main aim of this research is to propose a data caching strategies for the purpose of checking integrity constraints in a mobile environment. Two pre-fetch data caching strategies, namely: Blind Strategy (BS) and Relax Strategy (RS) which are embedded in the proposed framework were proposed for the purposed of checking integrity constraints in a mobile environment. The BS strategy blindly pre-fetch data caches into mobile host while RS strategy pre-fetch data cache by analyzing the relationships between integrity tests. These two strategies adopted the simplified form of integrity tests that are sufficient and complete tests. As a result, RS strategy reduced the amount of data items to be cached for the process of integrity constraints checking.